25.7k views
4 votes
Given that Q(x)=2x^2 +5x-3 find and simplify Q(a+h)-Q(a-h)

User Gmexo
by
6.1k points

1 Answer

5 votes

Answer:


Q(a+h)-Q(a-h)=8ah+10h

Explanation:

We are given the function:


Q(x)=2x^2+5x-3

And we want to find and simplify:


Q(a+h)-Q(a-h)

Substitute:


=[2(a+h)^2+5(a+h)-3]-[2(a-h)^2+5(a-h)-3]

Expand:


\displaystyle =[2(a^2+2ah+h^2)+5a+5h-3]-[2(a^2-2ah+h^2)+5a-5h-3]

Distribute:


=[2a^2+4ah+2h^2+5a+5h-3]-[2a^2-4ah+h^2+5a-5h-3]

Distribute:


=(2a^2+4ah+2h^2+5a+5h-3)+(-2a^2+4ah-2h^2-5a+5h+3)

Rewrite:


=(2a^2-2a^2)+(4ah+4ah)+(2h^2-2h^2)+(5a-5a)+(5h+5h)+(-3+3)

Combine like terms:


=8ah+10h

Hence:


Q(a+h)-Q(a-h)=8ah+10h

User Ludwig
by
5.5k points